Strategy to Increase the Yield of Fresh Fruit Bunch (FFB) Harvesting Process with Lean Agriculture Method at PTPN IV Palmco Regional II Marjandi Estate - Julyanda, Muhammad; Sembiring, Meilita Tryana; Absah, Yeni (Asian Journal of Management Analytics, 2025)
This study aims to identify Non Value Added (NVA) activities in the harvesting process of Fresh Fruit Bunches (FFB) and formulate optimization measures to improve operational efficiency and work productivity. Based on the results of field observation and work time analysis, eight activities were found that did not provide direct added value to the product, but contributed to the waste of time and resources. Optimization is carried out through a process improvement approach, including the elimination of unnecessary activities, improvement of workflows, the use of motorized tools, and the implementation of digitization of crop yield recording. The results of the implementation showed a decrease in the total harvesting process time from 23,560 seconds to 17,760 seconds, or an increase in time efficiency by 28.57%. These findings show that the systematic identification and reduction of NVA activities can improve operational performance and support the achievement of production targets in the palm oil industry.